1980
DOI: 10.1148/radiology.134.3.7355207
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic parenchymal patterns and risk factors for breast cancer.

Abstract: A classification scheme to mammographically identify women at high risk for breast cancer proposes four patterns of breast duct prominence: N1 (normal), P1, P2, and DY (dysplasia). The authors investigated the claims of several studies that women who later get breast cancer are more likely than controls to be in the P2 and DY categories, and attempted to determine whether parenchymal patterns are related to known epidemiological risk factors. Mammograms of the noncancerous breast of 102 women with cancer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…In two of these reports (Egan & Mosteller, 1977;Egan & McSweeney, 1979) differences in breastcancer incidence according to mammographic pattern in the cohort have been partly obscured by adding to them the prevalence of breast cancer observed at first examination, the latter possibly having been influenced by the referral bias described above. Two cohort studies have not confirmed Wolfe's findings (Moskowitz et al, 1980;Ernster et al, 1980) but in both there was a relatively small number of cases of breast cancer and a short follow-up.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In two of these reports (Egan & Mosteller, 1977;Egan & McSweeney, 1979) differences in breastcancer incidence according to mammographic pattern in the cohort have been partly obscured by adding to them the prevalence of breast cancer observed at first examination, the latter possibly having been influenced by the referral bias described above. Two cohort studies have not confirmed Wolfe's findings (Moskowitz et al, 1980;Ernster et al, 1980) but in both there was a relatively small number of cases of breast cancer and a short follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies report the incidence of breast cancer in a cohort of women classified according to their initial mammographic characteristics (Egan & Mosteller, 1977;Egan & McSweeney, 1979;Krook et al, 1978;Krook, 1978;Threatt et al, 1980;Moskowitz et al, 1980;Ernster et al, 1980). In others, the prevalence of breast cancer detected at the first examination within each category of mammographic pattern is described (Egan & Mosteller, 1977;Krook, 1978;Kessler & Fischedick, 1980).…”
mentioning
confidence: 99%
“…A further 19 studies were excluded from the main analysis, as they were not independent of other included studies (studies; refs. [8][9][10][11][12][13][14] as well as 12 studies from Breast Cancer Detection and Demonstration Project centers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) that were likely to have been subsets of two studies that included cases from all or most centers (2, 27), although they were considered in subgroup analyses. Four articles were found manually (28-31), giving a total of 42 included articles for the main analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, lobular carcinoma in situ is considered a strong risk marker of future breast cancer in both breasts (32,33), and there is recent evidence that ductal carcinoma in situ may also be associated with ipsilateral (OR, 1.9) and contralateral (OR, 2.0) breast cancer (34). Breast density is associated with several established risk factors for breast cancer, including positive associations with HRT, nulliparity, late age at first birth, alcohol intake, and inverse associations with age, postmenopausal status, and BMI (26,30,(35)(36)(37)(38)(39)(40). These risk factors account for only 20% to 30% of variation in breast density (26,28,29) and there is evidence that genetics and their interaction with environment likely account for the remaining variation (37,41).…”
Section: Discussionmentioning
confidence: 99%